Not in vain ; 17th what God hath wrought amongst the Kanakas in Queensland being Report of the Queensland Kanaka Mission for the year 1902-1903 (1903)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy. Missing cover.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history